Paleotethys slab pull, self-lubricated weak lithospheric zones, poloidal and toroidal plate motions, and Gondwana tectonics - Vizán, Haroldo (2017)
The Gondwana megacontinent was composed of different domains separated by self-lubricated weak lithospheric zones, two of which could have extended into Laurasia. Displacement vectors determined through three consecutive paleomagnetism-constrained paleogeographic reconstructions (Early Pennsylvanian-early Guadalupian, ca. 320-270 Ma; late Guadalupian-Middle Triassic, ca. 260-240 Ma; and Late Triassic-early Late Jurassic, ca. 230-160 Ma) show similar orientations to coeval tectonic stresses along Gondwana. Triggered by slab pull at the northern subduction margin of the Paleotethys Ocean, differential displacements between the Gondwana domains caused localized deformation along their borders, reactivating old weak lithospheric zones (e.g., Ventana fold belt south of Buenos Aries province, Argentina; basins such as Cuvette in central Africa; and Neuquén on the Pacific margin of Gondwana). We propose that the wide extent of these structures was possible due to the transmission of mantle toroidal flow induced by strike-slip movements along these focused self-lubricated weak lithospheric zones, along with the northward drift of Pangea. These processes occurred simultaneously with a major mantle reorganization from a huge cold downwelling to a hot upwelling event caused by thermal energy storage beneath Pangea.